Variabilidade genética em alface para agricultura orgânica - Oliveira, Natália Souza (2017)
The visual aspect of the lettuce is paramount for its acceptance by consumers. In organic agriculture, each farmer has a preference for some types of lettuce based on their market. However, there is no availability of organic seeds of lettuce nor cultivars adapted to this cropping system. The multivariate analysis of important traits for lettuce breeding would be useful to investigate the genetic variability of lettuce plants as well as to support the selection of plants with traits of interest. The present work was conducted in order to study the genetic variability of lettuce plants aiming at the organic cropping by using the principal component analysis and the hierarchical groupings. Thereafter, fictitious data of plants with phenotypes of interest were added to the analyses in order to graphically display both the distribution of progenies and the phenotypes, thus, assisting in the selection of progenies with the desired phenotypes. In addition to the parents – the cultivars Colorado and Salinas 88 –, the F1 and F2 populations along with the F2:F3 progenies from this crossing were used. A completely randomized block design with three replicates was used. The plots consisted of twelve plants. The following traits were evaluated: presence of anthocyanin, coloration, type of limb, type of border, and chlorophyll content. The two major components accounted for 75.27% of the data variation. The highest discrimination traits were chlorophyll content, types of limb, and border. By means of the principal component analysis, it was possible to observe the separation of the parents Colorado and Salinas, which are contrasting. The F1 generation was located between its parents. The F2:3 progenies had higher phenotypic variation than the F2 generation. The cultivar Colorado is the most divergent phenotype. According to the analyses of hierarchical groupings, 5 groups were formed and the progeny 31 was the most divergent genotype. Both methodologies were similar to some extent in the grouping of some genotypes, and there was genetic variability in population F2, mainly, F2:3 progenies. In general, the principal component analysis as well as the hierarchical groupings, added with plants with commercial standards, were not useful in the selection of plants with phenotypes of interest mostly because the genotypes were grouped based on their content of chlorophyll. Nevertheless, the visual selection of lettuce plants is feasible provided they are qualitative traits. Furthermore, there was genetic variability in this population, allowing the selection of plants based on their color and texture of leaves.